2013
DOI: 10.1186/1471-2407-13-354
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of serum CYFRA 21–1 in patients with advanced lung adenocarcinoma: a retrospective study

Abstract: BackgroundSerum CYFRA 21–1 is one of the most important serum markers in the diagnosis of non-small cell lung cancer (NSCLC), especially squamous-cell carcinoma. However, it remains unknown whether pretreatment serum CYFRA 21–1 values (PCV) may also have prognostic implications in patients with advanced lung adenocarcinoma.MethodsWe retrospectively reviewed the data of 284 patients (pts) who were diagnosed as having advanced lung adenocarcinoma and had received initial therapy.ResultsOf the study subjects, 121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…It is a unique epitope from a polypeptide and abundantly elaborated following cell death, whose diagnostic utility and prognostic relevance have been demonstrated in stomach cancer, colorectal cancer, breast cancer, and cervical cancer (Gaarenstroom et al, 1995;Lee, 2013;Wang et al, 2013;Gwak et al, 2014). Having been classified into 20 subtypes based on isoelectric point and differences in the molecular mass which was determined by 2-dimensional electrophoresis, Cyfra21-1 is a useful auxiliary biomarker in the diagnosis of NSCLC, and it has been reported that it has particularly high specificity for the diagnosis of lung squamous cell carcinoma (Ono et al, 2013). Therefore based on NSE, CEA and Cyfra21-1, the GEP1 accuracy is outstanding than GEP2 and GEP3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a unique epitope from a polypeptide and abundantly elaborated following cell death, whose diagnostic utility and prognostic relevance have been demonstrated in stomach cancer, colorectal cancer, breast cancer, and cervical cancer (Gaarenstroom et al, 1995;Lee, 2013;Wang et al, 2013;Gwak et al, 2014). Having been classified into 20 subtypes based on isoelectric point and differences in the molecular mass which was determined by 2-dimensional electrophoresis, Cyfra21-1 is a useful auxiliary biomarker in the diagnosis of NSCLC, and it has been reported that it has particularly high specificity for the diagnosis of lung squamous cell carcinoma (Ono et al, 2013). Therefore based on NSE, CEA and Cyfra21-1, the GEP1 accuracy is outstanding than GEP2 and GEP3.…”
Section: Discussionmentioning
confidence: 99%
“…Serum LDH levels have been correlated with poor prognosis and resistance to chemotherapy and radiotherapy in various neoplastic diseases (Zhao et al, 2013). Serum Cyfra21-1 is one of the most important serum markers in the diagnosis of nonsmall cell lung cancer (NSCLC), especially squamous-cell carcinoma (Ono et al, 2013;Wang et al, 2013). So, based on CEA and NSE, we set up three GEP models -GEP1 (CEA, NSE, Cyfra21-1), GEP2 (CEA, NSE, LDH), GEP3 (CEA, NSE, CRP).…”
Section: Biomarker Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYFRA 21-1 (fragment of cytokeratin 19) has been demonstrated as clinically useful in prognostication and monitoring of the patients with lung cancer. Elevated pretreatment values of CYFRA 21-1 in NSCLC patients reported to be associated with unfavorable prognosis [62]. Decreasing concentrations of CYFRA 21-1 in NSCLC predict objective response to treatment in advanced disease [63].…”
Section: Prognostic Biomarkersmentioning
confidence: 99%
“…Accelerated CK19 degradation occurs in neoplastically transformed epithelial cells as a result of increased protease activity of caspase 3, which is a regulator of the apoptosis cascade, and fragments are released into the blood. This leads to an increase in the serum CYFRA21-1 level, which can be recognized by two monoclonal antibodies [8]. CYFRA21-1 has been identified as a potential tumor marker for the diagnosis and prognosis of non-small-cell lung cancer (NSCLC).…”
mentioning
confidence: 99%